INTERPRETASI SEBARAN MINERALISASI LOGAM EMAS BERDASARKAN NILAI RESISTIVITY MENGGUNAKAN METODE GEOLISTRIK KONFIGURASI WENNER - Malik, Maulana; Nur, Irzal; Ilyas, Asran (Jurnal Penelitian Geosains, 2014)
The limitation of data and information about distribution of gold mineralization based on the value of resistivity in the hosted rock on WIUP exploration PT. Indi Karya Anugerah which is located in Long Iram, West Kutai, East Borneo becomes the background of this study. The purpose of this study is expected to find the indications of gold mineralization anomalies based on the geophysical data of geoelectrical resistivity value hosted rock, rock contacts, mineralization and the sub-surface distribution. Vertical geoelectrical resistivity inversion using Wenner configuration for eight line of one with the position of the potential electrode and current electrode arranged from C1-P1-P2-C2. Based on the result of resistivity interpretation using software RES2Dinv showed that the lowest resistivity value of materials is 1.23Î©m till the highest one is 119085Î©m with rocks encountered indicated as Latite which was exposed, had a high resistivity. Outcrop of alteration area was found with relatively low resistivity and based on its physical characteristics as well as indication of gold occurrences in rock samples with grade of 2.01 ppm on line 01-line 02 and 2.27ppm on line 08 which were the analysis result in laboratory.Keywords: Survey review, alteration, resistivity, software RES2Dinv, anomalies